The Relationship between Personality Structures and Moral Development: Mediating Role of Mind Reading in the Students of Farhangian University of Kerman - Mohammad Esmaeilzadeh; Hamdollah Manzari Tavakoli; Mitra Kamyabi; Amanollah Soltani (Iranian Journal of Educational Research)
Objective: The present investigation was conducted with the objective of exploring the relationship between personality structures, as conceptualized by the neo-approach, and moral development, taking into consideration the mediating role of mind reading. Methods: The research design employed a correlational method. The target population consisted of students enrolled at Farhangian University of Kerman in 2023. A sample size of 350 students was randomly selected using the random sampling technique. The research instruments employed in this study included the NEO-SF questionnaire, Cognitive Emotion Regulation Questionnaire and Lotfabadi's Moral Development Scale. Data analysis was performed using SPSS-19 and AMOS software. Results: The findings derived from path analysis demonstrated that the modified model, after the exclusion of non-significant paths, exhibited a satisfactory fit. Furthermore, the results indicated that the dimensions of mind reading ability significantly mediated the relationship between personality traits and moral development. Conclusions: Based on the outcomes of this investigation, it is recommended to incorporate the teaching of emotional understanding and mind reading skills as a means of enhancing moral development.